TINJAUAN ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI DALAM BIDANG ILMU STEGANOGRAFI - Naibaho, Frainskoy Rio (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Steganography is a field of science that studies the technique of hiding information in digital media to protect data from third-party detection ketiga (Atawneh et al., 2013; Michaylov & Sarmah, 2024; Sitompul et al., 2018). This article reviews steganography through three philosophical perspectives: ontology, epistemology, and axiology. Ontologically, steganography explains the existence of hidden information in host media and its interactions. Epistemology plays a role in the process of developing and validating knowledge related to hiding and detection techniques. Meanwhile, axiology highlights the ethical benefits and risks, including the use to protect privacy and the potential for misuse in cybercrime. Steganography, with this comprehensive understanding, plays an important role in data security and information technology.Keywords: Steganography, Ontology, Epistemology, and AxiologyAbstrak: Steganografi adalah bidang ilmu yang mempelajari teknik penyembunyian informasi di dalam media digital untuk melindungi data dari deteksi pihak ketiga (Atawneh et al., 2013; Michaylov & Sarmah, 2024; Sitompul et al., 2018). Artikel ini meninjau steganografi melalui tiga perspektif filosofis: ontologi, epistemologi, dan aksiologi. Secara ontologis, steganografi menjelaskan keberadaan informasi tersembunyi dalam media host dan interaksinya. Epistemologi berperan dalam proses pengembangan dan validasi pengetahuan terkait teknik penyembunyian dan deteksi. Sementara itu, aksiologi menyoroti manfaat dan risiko etis, termasuk penggunaan untuk melindungi privasi dan potensi penyalahgunaan dalam kejahatan siber. Steganografi, dengan pemahaman komprehensif ini, berperan penting dalam keamanan data dan teknologi informasi.Kata kunci: Steganografi, Ontologi, Epistemologi, dan Aksiologi